KEPEMIMPINAN DAN MOTIVASI PENGARUHNYA TERHADAP KEPUASAN KERJA KARYAWAN - Darmawan, Kusnanto (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2018)
The purpose of this study is to determine the influence of leadership and motivation partially and simultaneously to job satisfaction employees CV. Icon Teqnologi. The research type used is descriptive with causal associative approach. This study was conducted with the number of respondents as many as 35 people. The sampling technique used is a saturated sampling technique. Hypothesis testing is done by multiple linear regression analysis for hypothesis through SPSS 16 for windows program. Based on the results obtained in the study that partially influence the leadership of employee job satisfaction, while motivation has no effect on employee job satisfaction. But simultaneously leadership and motivation affect the employee job satisfaction. The amount of influence of leadership and work motivation on employee job satisfaction is shown by the value of determination (R2) of 0.33 while the rest of 67% influenced by other variables such as discipline, compensation, organizational culture and others.